Concepções de Ciência em narrativa de licenciados em Química no Amazonas - Nascimento, Gabriel Rodrigues do (2011)
The research investigates the concepts of science teachers in training, specifically in the Bachelor's Degree in Chemistry from the Federal Institute of Education, Science and Technology of Amazonas (IFAM). Has as general objective to demonstrate scientific concepts in students' narratives of the fourth period of the course of the IFAM in Chemistry for the activities arising from the implementation of discipline Science Education. The methodological procedures have been focused on participatory research, with its basic concepts and fundamental principles, provided with theories of different disciplines and practical experiences during a semester. The support of the research participant was given from the narrative research, which offers the emphasis and value the voices of people involved, with reference to context and the teaching-learning interactions that occurred during class. In the reports of events lived / experienced by individuals was valued what was recorded in his memoirs, which was significant and that, by telling, (re) built what they lived.